Microcirculation Disorders in Patients with Severe COVID-19 - E. E. Ladozhskaya-Gapeenko; K. N. Khrapov; Yu. S. Polushin; I. V. Shlyk; N. N. Petrishchev; I. V. Vartanova (Вестник анестезиологии и реаниматологии)
Impaired microcirculation due  to endothelial dysfunction in COVID-19  is considered  to be  the most important link in the pathogenesis of this disease. However, due  to  the  complexity of its  instrumental  assessment  in critically ill patients,  the data available  in  the  literature on specific manifestations of endothelial dysfunction are very contradictory.The objective:  to determine  the most characteristic capillaroscopic signs of microvascular disorders and  to assess  the  state of microcirculation regulation in patients with severe COVID-19.Subjects  and Methods. When admitted  to  the  intensive  care unit,  60 patients with  COVID-19  and  12  patients with chronic cardiovascular pathology without COVID-19 (Comparison Group) were examined. All patients underwent microscopy of the microcirculatory bed of finger nail bed; the following parameters were assessed: diameters of the venous, arterial and transitional parts of capillaries, height of capillary loops, density of capillaries per  1 mm of the  length of the perivascular zone,  the average  linear velocity of capillary blood  flow (LVCBF), and  thickness of the perivascular zone. The presence of avascular zones,  the number of capillaries in the visualized field with circulating aggregates in the lumen, and the shape of capillaries were taken into account.  In addition, an occlusion test using laser Doppler flowmetry was performed  in 32 patients with COVID-19. The maximum post-occlusive increase in blood flow at the moment of cuff deflation was assessed, as well as changes in the mean value of post-occlusive blood flow relative to the baseline within 3 minutes after cuff deflation.Results.  In 53 (88.3%) patients with COVID-19, abnormalities corresponding to chronic microcirculatory changes in the form of predominance of pathological capillary forms were detected. Microaggregates in the lumen of capillaries and decreased linear velocity of blood flow were revealed in 100% of cases. When comparing groups of patients with different outcomes, statistically significant differences were revealed between the LVCBF parameters (in the survivors -  354.35 ± 44.78 pm/sec, in the deceased - 278.4 ± 26.59 pm/sec), as well as between the values of the perivascular zones thickness  (95.35  ±  15.96 microns versus  159.93 ±  19.90 microns). The results of the post-occlusion  test revealed  a significant difference between the groups in terms of the maximum post-occlusion gain (39.42 ± 3.85 BPU in the group with a favorable outcome, 27.69 ± 3.19 BPU in the group with an unfavorable outcome, 47.23 ±  1.78 BPU in the control group). In both groups, there was no increase in this parameter relative to the initial blood flow. At the same time, in the control group, the average index of post-occlusive blood flow was higher than the initial level.Conclusions. Acute microcirculation disorders with decreased linear velocity of capillary blood flow, circulation of aggregates, increased thickness of the perivascular zone were detected in all patients with severe COVID-19 but especially in those with unfavorable outcomes. Vascular tone regulation disorders were manifested by the absence of reactive hyperemia in response to acute ischemia, as well as a decrease in maximal flow-induced increase. These changes fit into the concept of endothelial dysfunction. Signs of chronic microcirculation disorders in most patients increase the risk of severe COVID-19.